1996
DOI: 10.1086/177343
|View full text |Cite
|
Sign up to set email alerts
|

Cosmological Formation of Low-Mass Objects

Abstract: We investigate the early formation of bound objects with masses comparable to the cosmological Jeans mass (10^5 solar masses). We follow the growth of isolated spherically symmetric density peaks starting from the linear perturbative regime. The initial parameters correspond to density peaks of various widths and heights in a Cold Dark Matter cosmology. We use a one-dimensional spherical Lagrangian hydrodynamics code to follow the dynamical, thermal, and non-equilibrium chemical evolution of the gas. The syste… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
412
1
2

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 354 publications
(427 citation statements)
references
References 0 publications
12
412
1
2
Order By: Relevance
“…The basic properties of these socalled Population III (Pop III) stars have been reasonably well established, with the consensus that the first stars formed in dark matter "minihalos" on the order of 10 5 -10 6 M at high redshifts (Couchman & Rees 1986;Haiman et al 1996;Tegmark et al 1997). Numerical simulations of the collapse of primordial metal-free gas into these halos, where molecular hydrogen is the only available coolant, had suggested that the first stars were predominantly very massive, with M * 100 M and a top-heavy initial mass function (IMF; e.g., Bromm et al 1999Bromm et al , 2002Abel et al 2002;Bromm & Larson 2004;Yoshida et al 2006;O'Shea & Norman 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The basic properties of these socalled Population III (Pop III) stars have been reasonably well established, with the consensus that the first stars formed in dark matter "minihalos" on the order of 10 5 -10 6 M at high redshifts (Couchman & Rees 1986;Haiman et al 1996;Tegmark et al 1997). Numerical simulations of the collapse of primordial metal-free gas into these halos, where molecular hydrogen is the only available coolant, had suggested that the first stars were predominantly very massive, with M * 100 M and a top-heavy initial mass function (IMF; e.g., Bromm et al 1999Bromm et al , 2002Abel et al 2002;Bromm & Larson 2004;Yoshida et al 2006;O'Shea & Norman 2007).…”
Section: Introductionmentioning
confidence: 99%
“…At any given time (redshift) 1σ fluctuations of the density field correspond to the characteristic mass of a collapsing halo at that redshift. More massive halos correspond to rarer peaks (i.e., 2-3σ) of the density field; such halos are much rarer, but they constitute, at each redshift, the densest environments where the formation of the first collapsed objects took place [42,43]. In the early halo assembly process, baryons follow the DM halo potential well, without plying any relevant dynamical role.…”
Section: The Infancy Of the Giants: Seed Black Hole Formationmentioning
confidence: 99%
“…Our chemical model includes all relevant primordial chemical species: H, H + , H − , H 2 , H + 2 , e − , He, He + , He ++ , D, D + , and HD (Haiman et al 1996;Galli & Palla 2002). We also include the most important metal coolants-neutral and singly ionized C, Si, O, and Fe.…”
Section: Chemistrymentioning
confidence: 99%
“…The standard cosmological model (ΛCDM) predicts the first stars (Pop III) formed at redshifts z 20-30 in ∼10 6 M dark matter (DM) "minihalos" (e.g., Couchman & Rees 1986;Haiman et al 1996;Tegmark et al 1997) and this brought about an end to the cosmic dark ages. The cooling properties of H 2 , the most effective primordial gas coolant at temperatures below 10 4 K, set a characteristic mass scale of 100 M for Pop III stars (Abel et al 2000;.…”
Section: Introductionmentioning
confidence: 99%